Contribution of informal and institutional skills provisions on business inception and growth: evidence from manufacturing and service industries - Alam, Gazi Mahabubul; Parvin, Morsheda; Rahman, Md. Mahfuzur (Emerald Group Publishing, 2021)
Purpose: Criteria of skills and their schemata have evolved out of historical social practices. Interpretation of social events is guided and constrained by the prevailing rationality which itself reflects the dominant constellation of power. Hence, some argued that informal provision of skills delivery is the base of business growth. Upon the success of informal provision, institutional counterpart unethically grabs the market, kicking off the earlier. Evidences arguably confirmed that the institutional provision of skills delivery contributes to rapid business growth. Business growth is indeed important but not at the cost of exploitation of ethics which is the central focus of this study. Design/methodology/approach: Given the differentiated nature of research questions, multiple techniques are used to collect the data. However, this research adopts the norms of qualitative methods. Both secondary and primary data are used. While secondary data are collected through document reviews, primary data are collected via interviews. In total, 12 industries are sampled and equally distributed into two sectors (manufacturing and services). Findings: Findings show that the professional positions in the manufacturing industries at their inception phase were occupied by non-university graduates who received neither informal trainings nor on-the-job trainings. Over the time, university graduates started capturing the market. This has forced the non-university graduates to accrue a diploma from the universities in order to retain. Those who failed to obtain a university diploma are compelled to leave the sector. In fact, professional positions in service industries at the inception phase were mainly occupied by the university graduates who did not study the relevant subjects from the universities but received training from the informal provision. Later, universities started offering these programmes. Originality/value: A few studies have been published in the area of manufacturing industries especially on garments sector. None covers the paradigm transformation of skills (human capital theory) in garments. The authors also failed to locate a comparative study that maps the contribution of different provisions of skills providers and their paradigm transformations occurred within manufacturing and service industries. Therefore, this project explores the contribution of informal and institutional provisions of skills delivery for the inception and growth of industries by comparing between manufacturing and service industries.